PENERAPAN METODE PEMBELAJARAN THINK PAIR SHARE TERHADAP MENULIS TEKS EKSPOSISI PADA SISWA SMP - Majiah, Gina; Rahmah, Ashri Nurmalia; Rostikawati, Yeni (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This research is motivated by the lack of students' ability to write exposition texts in accordance with the structure and students tend to be difficult in making an exposition text. The researcher formulated the problem namely, whether the Think Pair Share method could improve students' ability to write exposition text. This study aims to determine whether there are differences in the value of writing exposition student text at the pretest and posttest stages using the Think Pair Share method. This study uses a one group pretest post-test design method. The results of student grades at the time of the pretest and posttest were treated using qualitative and quantitative analysis techniques. Quantitatively the researcher processes student grade data to look for mean scores and comparison of pre-test and post-test scores, while qualitative analysis techniques describe the results of student grade data. The sample in this study was class VIII, amounting to 30 students. The results showed that there was an increase in students' writing ability using the Think Pair Share method at the time of the posttest with the acquisition of an average that was greater than the pretest. The pretest obtained an average of 60, then at the posttest stage obtained an average of 80. Thus the use of Think Pair Share method is effectively used in exposition text writing activities because it can improve students' ability to write exposition text and can improve student grades.